The Role of School Administrators in Improving the Quality of Administrative Services - Alfandie, Alya Irzzaq Nahya; Juharyanto, Juharyanto; Prestiadi, Dedi (Universitas Negeri Malang, 2024)
Educational administration has an important role in supporting the smooth learning process in schools. School Administrative Personnel (TAS), who are included in non-teaching education personnel, are responsible for administrative tasks that support all school activities. In an effort to improve the quality of education services, TAS play a role in various fields such as academics, student affairs, personnel, finance, infrastructure, and public relations. Each of these roles includes administrative activities that ensure the effectiveness of school operations. The quality of these administrative services reflects the quality of educational services provided, which directly affects the learning process and educational outcomes. Adequate competencies and skills are required for TAS to ensure the success of school administration, which in turn improves the overall quality of education.